SOSIALISASI PEMBUATAN BRIKET ARANG DARI LIMBAH TONGKOL JAGUNG BAGI PARA PETANI DESA MUMBANG JAYA, KEC. JABUNG, KABUPATEN LAMPUNG TIMUR : SOCIALIZATION OF CHARCOAL BRIQUETTE MAKING FROM CORN COB WASTE FOR FARMERS IN MUMBANG JAYA VILLAGE, JABUNG DISTRICT, EAST LAMPUNG REGENCY - Anastiar Inayah; Afika Auliayi; Mela Liswida Sari; Anggun Maulida Arika Putri; Faska Ria Pangaribuan; Nisful Ardi; Fatih Izzudien Alqosam; Ridho Sholehurrohman; Igit Sabda Ilman (FMIPA Unila, 2025)
Corncob Charcoal Briquettes are a type of solid fuel that contains activated carbon, has a high calorific value, and burns for a long time. This study aims to process corncob waste into an alternative fuel in the form of briquettes. Additionally, briquettes made from corncob waste can increase economic value if sold and can boost the income of the community. The production of briquettes from corncob waste is done using tools such as a stove to heat tapioca paste, a bucket to mix the charcoal powder with the tapioca paste, and a sieve to separate coarse and fine particles. PVC pipes (polyvinyl chloride) are used to mold the briquettes, a pestle is used to grind the charcoal, and tapioca flour and water are added. Tapioca flour acts as a binder during the briquette-making process, and water helps dissolve the flour and strengthens the mixture of the binder and the charcoal. It is possible to convert agricultural waste into a cost-effective and environmentally friendly alternative energy source. Corncob charcoal briquettes are particularly beneficial, especially for people in rural areas such as Mumbang Jaya Village, because the production process is relatively easy and uses raw materials that are readily available. This initiative not only reduces the amount of waste generated but also opens up new economic opportunities for residents through the production of a marketable product. Keywords: Charcoal Briquettes, Corncob, Alternative Energy